Evans Blue Dye: A Revisit of Its Applications in Biomedicine - Ni, Y.; Yu, Peipei; Xue, Xing; Yao, Linpeng; Chen, Feng (Contrast media and molecular imaging, 2018)
Evans blue (EB) dye has owned a long history as a biological dye and diagnostic agent since its first staining application by Herbert McLean Evans in 1914. Due to its high water solubility and slow excretion, as well as its tight binding to serum albumin, EB has been widely used in biomedicine, including its use in estimating blood volume and vascular permeability, detecting lymph nodes, and localizing the tumor lesions. Recently, a series of EB derivatives have been labeled with PET isotopes and can be used as theranostics with a broad potential due to their improved half-life in the blood and reduced release. Some of EB derivatives have even been used in translational applications in clinics. In addition, a novel necrosis-avid feature of EB has recently been reported in some preclinical animal studies. Given all these interesting and important advances in EB study, a comprehensive revisiting of EB has been made in its biomedical applications in the review.